Effect of Feeding Diet Containing Different Dose of Vitamin E with 1:2 of n-3/n-6 Fatty Acid Content on Reproductive Performance of Female Zebrafish Danio rerio - Utomo, N.B.P; Nurjanah, N.; Setiawati, Mia (Indonesian Society of Scientific Aquaculture (ISSA), 2006)
The role of essential fatty acids as a precursor of prostaglandin and as a component of cell membrane in the form of phospholipids, can affect cell fluidity. Vitamin E functions as fatty acid antioxidant in the body and affects egg quality. Vitamin E and essential fatty acids (n-3 and n-6) are required at the same time in a proper ratio to induce fish gonad maturation. Zebra fish Danio rerio broodstock in 29 days pre-saline were fed on diet containing 4 different vitamin E concentration; i.e. 325, 375, 425 and 475 mg/kg diet with constant n-3 and n-6 fatty acid doses of 1% and 2%, respectively, for 6 weeks. Reproduction performance in terms of fecundity was improved (p